1980
DOI: 10.1103/physrevb.22.1663
|View full text |Cite
|
Sign up to set email alerts
|

Relativistic tight-binding calculation of core-valence transitions in Pt and Au

Abstract: The results of a relativistic tight-binding energy-band model for Pt and Au, utilizing parameters derived from Smith s empirically adjusted combined interpolation scheme, are applied to calculate the one-electron contribution to various x-ray and energy-loss spectra involving 4f and 2p core states in these materials. These results show that the unoccupied holes in the Pt 5d bands have predominantly j = 5/2 character (h», ) such that the (h5/2/A3/2) ratio ranges from -3.5 within 0.5 eV of EF to -2.9 over the en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
140
1

Year Published

1987
1987
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 256 publications
(152 citation statements)
references
References 22 publications
11
140
1
Order By: Relevance
“…The much smaller whiteline intensity near the edge in the L 2 data compared to the L 3 in transition metal samples is well-known and arises from spin-orbit interactions in the Pt 5d state and the preferred selection rules as illustrated in the insert of Figure 2. 12 The 5d 5/2 -5d 3/2 spin-orbital splitting is ∼1.5-2.5 eV in Pt, and the results reported here indicate this splitting depends on even the particle support. The L 3 edge reflects the empty levels of both the d 5/2 and d 3/2 bands weighted as d 5/2 /d 3/2 ≈ 6; 12 however, the L 2 edge reflects only the d 3/2 level.…”
Section: A Sample Preparation and Data Collectionmentioning
confidence: 66%
“…The much smaller whiteline intensity near the edge in the L 2 data compared to the L 3 in transition metal samples is well-known and arises from spin-orbit interactions in the Pt 5d state and the preferred selection rules as illustrated in the insert of Figure 2. 12 The 5d 5/2 -5d 3/2 spin-orbital splitting is ∼1.5-2.5 eV in Pt, and the results reported here indicate this splitting depends on even the particle support. The L 3 edge reflects the empty levels of both the d 5/2 and d 3/2 bands weighted as d 5/2 /d 3/2 ≈ 6; 12 however, the L 2 edge reflects only the d 3/2 level.…”
Section: A Sample Preparation and Data Collectionmentioning
confidence: 66%
“…1 [22]. The spin-orbit interaction in both core and valence levels introduces differences between the L 3 (2p 3/2 → 5d 5/2 , 5d 3/2 ) and L 2 (2p 1/2 → 5d 3/2 ) edges, both in shape and intensity (the 2p 3/2 -2p 1/2 splitting is around 1709 eV, and the 5d 5/2 -5d 3/2 splitting around is 1.5-2.5 eV [26]). The L 3 edge reflects the empty valence levels ( VB) of both d 5/2 and d 3/2 bands, weighted as d 5/2 /d 3/2 = 6 [26]; however, the L 2 edge reflects only the d 3/2 level.…”
Section: Analysis Of the Platinum L 3 And L 2 X-ray Absorption Edgesmentioning
confidence: 99%
“…5(c), it is shown that by combining the white line intensity measurements with the branching ratio measurements, all the Ni-silicide phases except NiSi and NiSi 2 can be distinguished. Mattheiss & Dietz (1980) and Pearson et al (1993) reported that the total white line intensity is proportional to the number of valence d holes. They also showed that in order to extract quantitatively the number of 3d electrons, the radial matrix elements for the excitations of the 2p 3/2 and 2p 1/2 core (Massalski, 1990).…”
Section: Total White Line Intensity Determinationmentioning
confidence: 99%
“…Pearson et al (1993) and Mattheiss & Dietz (1980) report a procedure by which EELS can provide information about the local occupation of 3d states in transition metals. They show that the sum of the intensities of the white lines (with the excitations to continuum removed) can be related to the occupancies of the corresponding outer d states.…”
Section: Introductionmentioning
confidence: 99%